Astragalus mongholicus Bunge Water Extract Exhibits Anti-inflammatory Effects in Human Neutrophils and Alleviates Imiquimod-Induced Psoriasis-Like Skin Inflammation in Mice - Cheng, Wei-Jen; Chiang, Chih-Chao; Lin, Cheng-Yu; Chen, Yu-Li; Leu, Yann-Lii; Sie, Jia-Yu; Chen, Wen-Ling; Hsu, Chung-Yuan; Kuo, Jong-Jen; Hwang, Tsong-Long (Frontiers in Pharmacology, 2021)
Neutrophils are the primary immune cells in innate immunity, which are related to various inflammatory diseases. Astragalus mongholicus Bunge is a Chinese medicinal herb used to treat various oxidative stress-related inflammatory diseases. However, there are limited studies that elucidate the effects of Astragalus mongholicus Bunge in human neutrophils. In this study, we used isolated human neutrophils activated by various stimulants to investigate the anti-inflammatory effects of Astragalus mongholicus Bunge water extract (AWE). Cell-free assays were used to examine free radicals scavenging capabilities on superoxide anion, reactive oxygen species (ROS), and nitrogen-centered radicals. Imiquimod (IMQ) induced psoriasis-like skin inflammation mouse model was used for investigating anti-psoriatic effects. We found that AWE inhibited superoxide anion production, ROS generation, and elastase release in human neutrophils, which exhibiting a direct anti-neutrophil effect. Moreover, AWE exerted a ROS scavenging ability in the 2,2‘-Azobis (2-amidinopropane) dihydrochloride assay, but not superoxide anion in the xanthine/xanthine oxidase assay, suggesting that AWE exhibited anti-oxidation and anti-inflammatory capabilities by both scavenging ROS and by directly inhibiting neutrophil activation. AWE also reduced CD11b expression and adhesion to endothelial cells in activated human neutrophils. Meanwhile, in mice with psoriasis-like skin inflammation, administration of topical AWE reduced both the affected area and the severity index score. It inhibited neutrophil infiltration, myeloperoxidase release, ROS-induced damage, and skin proliferation. In summary, AWE exhibited direct anti-inflammatory effects by inhibiting neutrophil activation and anti-psoriatic effects in mice with IMQ-induced psoriasis-like skin inflammation. Therefore, AWE could potentially be a pharmaceutical Chinese herbal medicine to inhibit neutrophilic inflammation for anti-psoriasis.